Determinants, Inequalities and Geographical Differences in Cognitive Performance Amongst the Elderly Population in South Korea - Sylvia Szabo; Malay Pramanik; Sayem Ahmed; Kevin Lesson (ACHSM, 2023)
Using the most recent 2018 Korean Longitudinal Study of Aging (KLoSA) survey data, this study aimed to examine the key determinants of cognitive impairment (CI) and to explore the inequalities and geographic differences of CI amongst the South Korean elderly population. The findings show that being super-aged, poor general health, and lack of exercise are positively associated with CI, while household wealth, educational level, participation in social activities and regular exercise all have a significant negative effect on CI. Compared to males, female respondents are more likely to experience CI. We found little difference between the specific determinates for the two subsamples. Inequalities in the prevalence of cognitive impairment were greatest in rural areas as well as amongst the respondents living in the Chungcheong region, Seoul Metropolitan Area and the Kangwan region. The results are helpful for the early intervention and prevention strategies to tackle the cognitive impairment problems of the elderly.